2022
DOI: 10.1097/brs.0000000000004542
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Randomized Control Trial to Compare the Role of Injection Cerebrolysin for 10 Days Duration Against Placebo in Operated Cases of Degenerative Cervical Myelopathy

Abstract: Study Design. Prospective randomized control trial. Objective. To analyze outcomes following the injection of cerebrolysin in surgically treated patients with degenerative cervical myelopathy (DCM). Summary of Background Data. Previous research has concluded that superior functional outcomes are achieved with the use of cerebrolysin in surgically treated patients of DCM for 21 days. Our study has been conducted to analyze the use of this drug for a shorter duration (10 days) and compare its clinical effica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Expanding on their prior work, Sharma et al sought to compare the clinical efficacy of postoperative Cerebrolysin delivered over a shorter duration (10 days). In a prospective RCT of 90 operatively treated cases of degenerative cervical myelopathy randomized into 2 groups, both groups experienced improvement in the mJOA score and the visual analog scale (VAS) score for pain at all time points; however, the Cerebrolysin group demonstrated a significantly greater mJOA score (16.37 ± 1) when compared with placebo (15.2 ± 1.8) at the 1-year follow-up (p < 0.0001) 7 . The authors also found neurological improvement in the Cerebrolysin treatment group to be superior (p = 0.04).…”
Section: Cervical Degenerative Conditionsmentioning
confidence: 99%
“…Expanding on their prior work, Sharma et al sought to compare the clinical efficacy of postoperative Cerebrolysin delivered over a shorter duration (10 days). In a prospective RCT of 90 operatively treated cases of degenerative cervical myelopathy randomized into 2 groups, both groups experienced improvement in the mJOA score and the visual analog scale (VAS) score for pain at all time points; however, the Cerebrolysin group demonstrated a significantly greater mJOA score (16.37 ± 1) when compared with placebo (15.2 ± 1.8) at the 1-year follow-up (p < 0.0001) 7 . The authors also found neurological improvement in the Cerebrolysin treatment group to be superior (p = 0.04).…”
Section: Cervical Degenerative Conditionsmentioning
confidence: 99%